Pendidikan Gizi Berbasis Media Sosial pada Calon Pengantin dalam pencegahan Stunting di Kotamobagu - Sarman Mustamin; Moh. Rizki Fauzan (Universitas Gorontalo, 2022)
Stunting is still a health problem in the world especially Indonesia. Stunting is a chronic malnutrition problem caused by lack of nutritional intake for a long time, resulting in growth disorders in children, namely the child's height is lower or shorter (short) than the standard age. The purpose of this study was to see the effect of social media-based nutrition interventions in increasing knowledge and attitudes of stunting prevention among brides. This type of research is a quasi-experimental study pre-post-test control group design. This research is concerns how an intervention affects the research object. Sample in this study were prospective brides who were already registered at KUA in Kotamobagu totaling 60 brides and grooms, 30 respondents intervention group and 30 respondents control group who were selected by purposive sampling. The results of Wilcoxon analysis in intervention group showed that knowledge and attitude variables before and after intervention, knowledge variable 0,000 and attitude variable 0,000, there was a significant difference. In the control group, knowledge 0,660 and attitude 0,080, there is no significant difference. The results of Mann Whitney test analysis in intervention group before and after treatment of knowledge and attitude variables, showed knowledge 0,000 and attitude 0,000, there was significant difference, in control group knowledge 0,131, attitude 0,132, there is no significant difference. In this study, social media-based nutrition education was proven to increase knowledge and attitudes of brides-to-be in preventing stunting. It’s hoped the Health Office and KUA will increase health promotion efforts in preventing stunting for brides.